Diversity and Abundance of Insect on Shallot (Allium Ascalonicum L.) with Integrated Pest Management (IPM) and Conventional Patterns - Manna, Dorkas Wantiawati; Afandhi, Aminudin; Tarno, Hagus (Direktorat Riset dan Pengabdian Masyarakat, Universitas Brawijaya, 2021)
Research on diversity and abundance of insect on shallot with Integrated Pest Management (IPM) and conventional patterns has been carried out. This study aims to analyze diversity and abundance of insects, damage level of shallot, and relationship between diversity and abundance of insects with growth and production of shallot in IPM and conventional land. This research was conducted in Junrejo village, Batu City in September to December 2017 while identification of insect was carried out at the Laboratory of Plant Pest and Disease, University of Brawijaya. This study uses Yellow pan trap and Pitfall trap methods. The result showed diversity index (H') of IPM land was 2.50 and of conventional land was 2.67, which both are moderate diversity. The abundance of insect on IPM land is higher (8672 individuals) compared to conventional land (3475 individuals). The level of crop damage is lower in IPM land compared to conventional land, while shallot growth and production is higher in IPM land compared to conventional land.